Multilab Direct Replication of Flavell, Beach, and Chinsky (1966): Spontaneous Verbal Rehearsal in a Memory Task as a Function of Age - Elliott, Emily M.; Morey, Candice C.; AuBuchon, Angela M.; Cowan, Nelson; Jarrold, Chris; Adams, Eryn J.; Attwood, Meg; Bayram, Büşra; Beeler-Duden, Stefen; Blakstvedt, Taran Y.; Büttner, Gerhard; Castelain, Thomas; et al. (Advances in methods and practices in psychological science, 2021)
Work by Flavell, Beach, and Chinsky indicated a change in the spontaneous production of overt verbalization behaviors when comparing young children (age 5) with older children (age 10). Despite the critical role that this evidence of a change in verbalization behaviors plays in modern theories of cognitive development and working memory, there has been only one other published near replication of this work. In this Registered Replication Report, we relied on researchers from 17 labs who contributed their results to a larger and more comprehensive sample of children. We assessed memory performance and the presence or absence of verbalization behaviors of young children at different ages and determined that the original pattern of findings was largely upheld: Older children were more likely to verbalize, and their memory spans improved. We confirmed that 5- and 6-year-old children who verbalized recalled more than children who did not verbalize. However, unlike Flavell et al., substantial proportions of our 5- and 6-year-old samples overtly verbalized at least sometimes during the picture memory task. In addition, continuous increase in overt verbalization from 7 to 10 years old was not consistently evident in our samples. These robust findings should be weighed when considering theories of cognitive development, particularly theories concerning when verbal rehearsal emerges and relations between speech and memory.